A comparison of the dose distributions from three proton treatment planning systems in the planning of meningioma patients with single‐field uniform dose pencil beam scanning. (8th January 2015) - Doolan, Paul J.; Alshaikhi, Jailan; Rosenberg, Ivan; Ainsley, Christopher G.; Gibson, Adam; D'Souza, Derek; Bentefour, El Hassane; Royle, Gary
Abstract : With the number of new proton centers increasing rapidly, there is a need for an assessment of the available proton treatment planning systems (TPSs). This study compares the dose distributions of complex meningioma plans produced by three proton TPSs: Eclipse, Pinnacle 3, and XiO. All three systems were commissioned with the same beam data and, as best as possible, matched configuration settings. Proton treatment plans for ten patients were produced on each system with a pencil beam scanning, single‐field uniform dose approach, using a fixed horizontal beamline. All 30 plans were subjected to identical dose constraints, both for the target coverage and organ at risk (OAR) sparing, with a consistent order of priority. Beam geometry, lateral field margins, and lateral spot resolutions were made consistent across all systems. Few statistically significant differences were found between the target coverage and OAR sparing of each system, with all optimizers managing to produce plans within clinical tolerances ( D 2 < 107 % of prescribed dose, D 5 < 105 %, D 95 > 95 %, D 99 > 90 %, and OAR maximum doses) despite strict constraints and overlapping structures. PACS number: 87.55.D‐